Highly stable cycling of a lead oxide/copper nanocomposite as an anode material in lithium ion batteries1. Issue 62 (8th July 2015) - Li, Cheng-Hung; Sengodu, Prakash; Wang, Di-Yan; Kuo, Tsung-Rong; Chen, Chia-Chun
<x xml:space="preserve">Abstract</x> Nanostructure composites of PbO/Cu–C were synthesized by in situ solvothermal synthesis and heat treatment of PbO/Cu with PVP, used as lithium battery anodes. It exhibits >90% capacity retention after 9500 cycles at a current density of 5.5 A g−1.